Exploring the Influence of Digital Marketing Strategies on Product Promotion - Lesnic, Ana (Digital Repository of Theses, 2025)
In this paper, the effect plays the role of global marketing strategy in companies for effective brand promotion, market expansion and product sales. Also, the analysis of strategies used by Samsung Apple is carried out, where we consider specific marketing steps. Thanks to the comparative analysis, which will be presented in a tabular form, we will see the approach to digital marketing between the two companies. The study concerns various marketing channels. We also consider the fundamental and historical aspects of digital marketing to ensure the operation of the advantages and trends that exist in digital marketing. In the future, different approaches will be studied, data research is aimed at identifying the most effective strategies and methods to create a brand story, increase the effectiveness of product sales, and achieve success through marketing Keywords: Digital Marketing, Internet, Internet marketing, SMM, Strategies, advantages and Disadvantages of Digital Marketing, Contextual Advertising.